Association between Respiratory Morbidity and Labor in Pregnancies with Gestational Diabetes Mellitus - Yu, Hope Y.; Has, Phinnara; Clark, Melissa A.; Esposito, Matthew; Rouse, Dwight J.; Werner, Erika F. (American Journal of Perinatology, 2020)
Objective This study aimed to the assess risk of respiratory morbidity in neonates born to women with gestational diabetes mellitus (GDM) delivered after labor compared with those delivered without exposure to labor.Study Design This is a secondary analysis of a prospective single-center cohort study of singleton pregnancies complicated by GDM. Neonates who were liveborn and delivered at ≥34 weeks' gestation were included. The primary outcome was respiratory morbidity defined as respiratory distress syndrome (RDS) or transient tachypnea of the newborn (TTN) resulting in neonatal intensive care unit (NICU) admission. Neonates born after labor (either spontaneous or induced) were compared with those delivered by cesarean delivery without labor. Associations between labor and neonatal morbidities were estimated using logistic regression. Covariates were adjusted for if they differed significantly between neonates exposed to and not exposed to labor (p < 0.05) and there was biologic plausibility that they would affect neonatal respiratory morbidity.Results Of the 581 neonates meeting study inclusion criteria, 23.2% delivered without exposure to labor. Those who did and did not experience labor delivered at similar gestational ages (38.6 vs. 38.4 weeks). Thirty-six neonates (6.2%) developed RDS or TTN and were admitted to the NICU. Exposure to labor was associated with a lower frequency of respiratory morbidity requiring admission to NICU, 4.9% (22/446) versus 10.4% (14/135) (p = 0.04). After adjusting for parity, body mass index, birth weight, gestational weight gain more than Institute of Medicine guidelines, race, and exposure to labor were associated with an adjusted odds ratio of 0.41 (95% confidence interval: 0.18–0.89).Conclusion Exposure to labor was associated with decreased odds of respiratory morbidity in neonates born to mothers with GDM. Limiting elective cesarean in this population can reduce health care costs and optimize neonatal health.Key Points
Keywords: cesarean delivery; gestational diabetes; labor; neonatal respiratory morbidity